2019
DOI: 10.1016/bs.mie.2018.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Sortase-mediated fluorescent labeling of CRISPR complexes

Abstract: Fluorescent labeling of proteins is a critical requirement for single-molecule imaging studies. Many protein labeling strategies require harsh conditions or large epitopes that can inactivate the target protein, either by decreasing the protein's enzymatic activity or by blocking protein-protein interactions. Here, we provide a detailed protocol to efficiently label CRISPR-Cas complexes with a small fluorescent peptide via sortase-mediated transpeptidation. The sortase tag consists of just a few amino acids th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We explored a Sortase A-mediated labeling strategy to fluorescently label Tau protein while causing minimal perturbation at the core region of the protein in the fibrillar state. The method relies on the addition of a specific recognition motif LPXTG (X being any amino acid) to the C terminus of recombinantly expressed Tau protein. Sortase A from Staphylococcus aureus cleaves off the terminal glycine and forms a thioester with threonine.…”
Section: Resultsmentioning
confidence: 99%
“…We explored a Sortase A-mediated labeling strategy to fluorescently label Tau protein while causing minimal perturbation at the core region of the protein in the fibrillar state. The method relies on the addition of a specific recognition motif LPXTG (X being any amino acid) to the C terminus of recombinantly expressed Tau protein. Sortase A from Staphylococcus aureus cleaves off the terminal glycine and forms a thioester with threonine.…”
Section: Resultsmentioning
confidence: 99%
“…We first assayed how Polθ-h counteracts RPA-coated ssDNA because RPA inhibits hybridization of heteroduplex oligos during TMEJ (19). We monitored the removal of fluorescent RPA-GFP because multiple fluorescent labeling strategies resulted in hypoactive Polθ-h ( Figure S2A ) (39). In this assay, ssDNA curtains are assembled with RPA-GFP.…”
Section: Resultsmentioning
confidence: 99%
“…Single-tethered DNA curtains were also combined with biochemical assays to gather more molecular details about Abo1-mediated histone loading onto DNA and the ongoing interactions between Abo1 and DNA [112]. Another study combined single-tethered and double-tethered DNA curtains to monitor the motion of individual fluorescently labeled Type I-E CRISPR-Cas proteins on DNA [113]. It revealed that Cas1-Cas2 integrase is able to non-specifically sample the DNA through 3D collisions with a short lifetime, while Cas3 helicase/nuclease translocates on DNA by using two main modes, as at the target sequence it either moves in conjunction with the 11-subunit crRNA-containing Cascade surveillance complex or independently away from Cascade.…”
Section: Single-tethered Dna Curtainsmentioning
confidence: 99%